RESIDENTS’ PERCEPTIONS OF TOURISM IN RELATION TO THEIR PERSONAL WELL-BEING - Daniela Soldic Frleta; Jelena Durkin Badurina; Ljiljana Kaliterna Lipovcan (Enlightening Tourism: A Pathmaking Journal)
This study examines the relationships between residents' perceptions of tourism and their overall personal well-being. In addition, the study aims to find out what differences exist in the perception of personal well-being and the impact of tourism between residents who provide private accommodation for tourists and those who do not.